Genre Analysis of Body Horror in Contemporary Hollywood Films (The Substance, Bodies Bodies Bodies, and It’s What’s Inside) - Aulia Rahmawati; Farrel Rakha Adi Pramana (Lavish Opulent Education, 2025)
This article examines the dynamics of the body horror genre in three recent Hollywood films: The Substance (2024), Bodies Bodies Bodies (2022), and It’s What’s Inside (2024). Utilizing Nick Lacey’s